Performance Improvement Analysis of Micro-Enterprises: Outcomes from Field Survey of Kavre District (Pravaha, 2025)
This research aims to analyze influence of Micro-Enterprise Development (MED) model implemented by the Ministry of Industry (MoI) in the performance of micro-enterprise. Kavrepalanchowk district has been purposively sampled for the study whereas micro-entrepreneurs are sampled using systematic random sampling. A Descriptive research design is used for this study. This study has used mixed approach while analyzing data. The opinion survey of micro-entrepreneurs is based on structured questionnaires constructed using Five-point Likert Scale. Most of the publication reports from websites of the Ministry of Industry and UNDP are collected as sources of secondary data and primary data has been collected from field visit. Both the descriptive and inferential dataanalyses have been undergone using SPSS. Analysis have revealed that the MED model is effectively supportive for the performance improvement of micro-enterprises. From the outcome of this study, it is concluded that the MED model is appropriate to be replicate by other private and non-government sector entrepreneurship and skill training providers as well as Nepal Government’s other programs for skills and employment generation.